Hysteretic behavior of repaired C-shaped concrete filled-composite plate shear walls (C-PSW/CF). (15th August 2021) - Kizilarslan, Emre; Bruneau, Michel
Highlights: Demonstrated hysteretic flexural behavior of repaired C-PSW/CF under flexure and axial loads. No repair strategy had been formulated and verified for C-PSW/CF. This paper proposes a structural repair scheme for C-PSW/CF and examines its effectiveness. Abstract: Composite Plate Shear Wall/Concrete Filled (C-PSW/CF) have been the subject of much recent research for application as core-walls in high-rise construction. This lateral-force resisting system consists of steel plates connected with tie bars and "sandwiching" concrete between them. Previous tests on C-shaped C-PSW/CF walls Kenarangi et al. (2020) that were subjected to flexure and axial loads together showed a good cyclic behavior without premature strength degradation. For the specimens tested, axial load as high as 19% of the crushing load of the infill concrete ( Ac f ′ c ) was applied. Also, ductility was observed to be more than 4 when flexural strength dropped to 80% of its peak values. Another perceived advantage of these type of walls was that repair was believed to be easier to repair following earthquake damage, but no repair strategy had been formulated and verified in the past. The availability of a damaged specimen as a results of the Kenarangi et al. (2020) tests provided an opportunity to develop a proposed structural repair scheme and investigate it effectiveness. Such a repair scheme was implemented on one of the damaged specimens that was then retested. The repair process and results from testing of that repaired specimen are presented in this paper.